2011
DOI: 10.2460/javma.238.7.905
|View full text |Cite
|
Sign up to set email alerts
|

Duration of clinical signs prior to total hip replacement in dogs

Abstract: Between 1992 and 2009, the duration of clinical signs prior to THR in dogs increased significantly. In dogs that underwent bilateral THR, the interval between surgeries was shorter than the duration of clinical signs before the first THR. Developments in medical treatments of osteoarthritis, surgical preferences, and veterinarian recommendations may influence the interval between initial clinical signs and surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…A recent veterinary report indicated that the duration between time at onset of clinical signs associated with coxofemoral OA, to the time of examination for THR increased in recent years by comparison with when THR initially became available for dogs . It was speculated that the increasing number and availability of nonsurgical treatment options, such as cyclooxygenase‐2‐selective NSAID, nutraceutical products and prescription diets, was responsible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent veterinary report indicated that the duration between time at onset of clinical signs associated with coxofemoral OA, to the time of examination for THR increased in recent years by comparison with when THR initially became available for dogs . It was speculated that the increasing number and availability of nonsurgical treatment options, such as cyclooxygenase‐2‐selective NSAID, nutraceutical products and prescription diets, was responsible.…”
Section: Discussionmentioning
confidence: 99%
“…Increased anesthesia and surgery time associated with more complex delayed surgeries can also predicate increased infection rate . In dogs, it has been proposed that delaying surgical intervention may increase propensity for postsurgical complications, may render surgical intervention more technically challenging because of paucity of acetabular rim or cortical drift of the proximomedial femoral cortex, may contribute to poor postoperative function, and may preclude THR with standard implants . Recent reports of dorsal acetabular rim augmentation techniques bear testament to this .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 79 There are no clear guidelines for the best time to implement total hip replacement, but the average time between onset of signs and surgery is 10 months. 80 Total hip replacement procedures in dogs began in the 1970s, and a modular system was introduced in the mid 1990s that coupled a fixed monobloc cobalt-chromium alloy femoral implant with an acetabular cup for cemented fixation. 81 Further refinements to total hip replacement implants have contributed to a high clinical recovery rate, with loosening of the acetabular cup and cup wear reported as some of the most common complications.…”
Section: Therapeutic Management and Interventionmentioning
confidence: 99%